ХУДОЖНІЙ ДОСВІД ЯК ЦІЛІСНИЙ ШЛЯХ ОСЯГНЕННЯ ІСТИНИ (Педагогіка вищої та середньої школи, 2006)
Esihencal experience as a integral way comprehension of truth. By specifying the notion of essential unity and peadianty af the philosophical and aesthetic thinking, the author considers esthetical experience as a harmonically united logic-rational and miagmalmluitive comprehension of truth.